The role of composition on the extent of individual strengthening mechanisms in polycrystalline Ni-based superalloys. (5th July 2019) - Goodfellow, A.J.; Galindo-Nava, E.I.; Schwalbe, C.; Stone, H.J.
Abstract: Models of the multiple strengthening mechanisms operating concurrently in nickel-based superalloys have been combined to provide predictions of the overall yield strength. Although these are established models, when all of the individual strengthening mechanisms were taken into account, it was found that these models did not compare well in magnitude to experimental data for the yield strength of several commercial alloys, although the trends were well described. To further explore the capability of these models, the role of composition on each of the individual strengthening mechanisms was investigated for the commercial alloy RR1000. Composition was found to have a complex role on the yield strength due to the multifaceted effect of elemental phase partitioning. The methods described may be collectively used to refine alloy composition and microstructure for optimal strength. Graphical abstract: Unlabelled Image Highlights: The extents of the multiple underlying strengthening mechanisms of Ni-based superalloys were modelled. Current models don't accurately predict the magnitude of the yield strength of alloys when multiple mechanisms are included. Composition has a complex effect on strengthening mechanisms due to the multifaceted effect of elemental phase partitioning. Precipitation is the most significant strengthening mechanism and is strongly linked to the size and fraction of tertiary γ′.